2018
DOI: 10.1097/j.pain.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Color-selective photophobia in ictal vs interictal migraineurs and in healthy controls

Abstract: Aversion to light is common among migraineurs undergoing acute attacks. Using psychophysical assessments in patients with episodic migraine, we reported that white, blue, amber, and red lights exacerbate migraine headache in a significantly larger percentage of patients and to a greater extent compared with green light. This study aimed at determining whether these findings are phase-dependent-namely, manifested exclusively during migraine (ictally) but not in its absence (interictally), or condition-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…This conclusion is heavily supported by the notion that color perception is generated by the visual cortex in response to signals that originate in retinal cones [11]. Along this line, we also suggested that because the generation of color perception and its processing depend on color-sensitive, cone-opponent neurons in the visual cortex [11], the most reasonable way to explain why control subjects like colored light whereas migraineurs find colored light aversive is by abnormal functioning of the visual cortex [25].…”
Section: Introductionsupporting
confidence: 58%
“…This conclusion is heavily supported by the notion that color perception is generated by the visual cortex in response to signals that originate in retinal cones [11]. Along this line, we also suggested that because the generation of color perception and its processing depend on color-sensitive, cone-opponent neurons in the visual cortex [11], the most reasonable way to explain why control subjects like colored light whereas migraineurs find colored light aversive is by abnormal functioning of the visual cortex [25].…”
Section: Introductionsupporting
confidence: 58%
“…Exposure to green light may modulate nociception and anxiety. Non-green light stimuli exacerbated pain intensity during the migraine attack but not in healthy control [55]. In contrast, exposure to green light reduced pain intensity in ~ 20% of the patients (18/69 CM) [56].…”
Section: Green Lightmentioning
confidence: 85%
“…To investigate the wavelength specificity of trigeminal phototoxicity, we explored the impact of narrow 10 nm wavebands situated within the large blue-green spectrum. We chose the violet (410 nm) and the blue (440 nm) wavelengths known to be harmful for the retina [28,29], the turquoise blue (480 nm) implicated in circadian rhythms [30], the green light (510 nm) reported to be soothing for photophobic migraineurs [31,32] and also the red light (630 nm). The part of the plate was kept in the dark for the control condition; the red-illuminated part served as a second control since, to our knowledge, there are no data about any damage from red-light exposure.…”
Section: Discussionmentioning
confidence: 99%